Review and proposal of indicators (key performance indicators) for library and social media - Fernández Villavicencio, Nieves; Menéndez Novoa, José Luis; García, Catuxa Seoane; Millán Fernández, María Elvira (Revista española de documentación científica, 2013)
The objective of this paper is to review the literature about systems of measure in social networks and present a draft proposal of set of indicators to help the units of information to evaluate the use and impact of their services through social Web o Web 2.0,with the aim to obtain cost and return of investment (ROI) of such services. Libraries have a long way in evaluation process but,in this article,we propose to evaluate the ROI and offer to organizations that support the units of information or libraries,the justification in order to demonstrate the added value they provide with social Web. © 2013 CSIC.
[Revisión y propuesta de indicadores (KPI) de la biblioteca en los medios sociales]
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 4 - Educación de calidad